Hearing gain in tympanoplasty type I , Lic. Luis Donaldo Colosio Murrieta Northwest Specialty Hospital Nº2 - Gómez Rodriguez, Enrique (2016)
Objective: To determine if there is a hearing gain after performing a tympanoplasty type 1 in patients with mid level chronic otitis and conductive hearing loss. Material and Methods: This study was conducted in the otolaryngology service of the Specialty Hospital Nº2, highly specialized medical unit, Northwest National Medical Center in Obregon city, Sonora. A study of a retrospective, analytical and longuitudinal cohort was carried out. Overview of the Study: Clinical records of patients diagnosed with sequale of mid level chronic otitis, tympanoplasty type 1 post surgery patients in this institution from March 2011 to April 2014 were reviewed. Data such age, sex and place of origin were taken and if there were any post surgery complications, average level of hearing previous and after surgery. Results: From a total of 237 reviewed patients, 51 were completed, of which 33 were female (64.7%), range of age was fron 9 to 71 years old with an average of 36.7 years old.The most frequent operated side was the right in 33 patients (64.7%). No complications in the files reviewed were found. In the evaluation of audiometry previous the surgery, certain degree of hearing loss was observed in 46 patients (90.19%) and normal in 5 patients (9.8%). Postsurgically an standard audiometry were foun in 38 patients (74.5%) and anormal in 13 patients (25.49%) with p<.0001. There is a statistically significant hearing gain with tympanoplasty type 1 in patients with sequale of mid level chronic level in the highly specialized medical unit, Northwest National Medical Center in Obregon city, Sonora. Conclusions: In most of our patients tympanoplasty type 1, there was an improvement in hearing. This results are similar to those found in authors such as Shrestha and et al.><.0001. There is a statistically significant hearing gain with tympanoplasty type 1 in patients with sequale of mid level chronic level in the highly specialized medical unit, Northwest National Medical Center in Obregon city, Sonora. Conclusions: In most of our patients tympanoplasty type 1, there was an improvement in hearing. This results are similar to those found in authors such as Shrestha and et al.